Spectrophotometric determination of Mefenamic acid viadiazo coupling reaction using different reagents in dosage forms - Hasan, Shlear H. (Sulaimani Journal for Pure and Applied Sciences, 2016)
Three simple, accurate and precise spectrophotometric methods were proposed for determining of mefenamic acid in pure form as well as in dosage forms. The proposed methods were based on the coupling of mefenamic acid with diazotized 4-aminohippuric acid, 4-nitroaniline and 4-aminoantipyrine in alkaline medium for methods A, B and C, respectively. The colored azo dyes were quantitated photometrically at 432, 453, and 406 nm for methods A, B and C, respectively. Different variables affecting the reactions were optimized. Beer’s law was obeyed over the concentration ranges of 0.5-20, 1.0-16 and 0.2-14 μg/ml for methods A, B, and C, respectively. The colored azo dyes remained stable for more than 3 hours in the three methods. The proposed methods were applied successfully to determine mefenamic acid in dosage forms.
Keywords: Mefenamicacid; Spectrophotometry; dosage forms,Diazo coupling reaction